APLIKASI HADIST AKAD MUROKKABAH DARI TEKS KE KONTEKS - Azidni Rofiqo (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2018)
The problem of understanding hadith is urgent, because it lays as second primary reference of Islamic teachings after the Qur'an. Many communities fail to understand the hadith comprehensively, because in fact many Islamic financial institutions apply al-'uqud al-murokkabah, while the text of hadith said that al-'uqud murokkabah is haram. The form of this research is descriptive qualitative that is deductive, which focuses first on criticism on sanad and matan hadith, and second on it’s tafsir The results of this study by criticism of sanad and matan hadith are that it’s qualification is hasan sohih which can be used as a guide to determine jurisprudence law. And it’s result through hermeneutic interpretation on hadith using Abdullah Saeed's method is if the contract of al ‘uqud al murokkabah becomes the cause of riba, gharar and maysir, so that this contractbecomes haram. If al ‘uqud al murokkabah does not become the cause of riba, gharar and maysir, so that this contract becomes legitimated, because it will be economic justice